Some sufficient conditions for univalence - Sukhjit Singh (International Journal of Mathematics and Mathematical Sciences)
A new subclass R(α), 0≤α≤1, of the class St(1/2) the class of starlike functions of order 1/2 is introduced and it is shown that R(α) is closed with respect to the Hadamard product of analytic functions. Some sufficient conditions for the normalized regular functions to be univalent in the unit disk E are given.